Long-term fertilization has different impacts on bacterial communities and phosphorus forms in sugarcane rhizosphere and bulk soils under low-P stress - Wu, Qihua; Chen, Diwen; Zhou, Wenling; Zhang, Xingxing; Ao, Junhua (Frontiers in Plant Science, 2022)
The application of phosphorus (P) fertilizer effectively improves soil P availability, but it also affects soil microbial communities. However, the responses of soil bacterial communities and P forms to long-term P fertilization, and the relationships of bacterial communities with soil P forms remain unclear in P-deficient field. In this study, the impacts of different P fertilization treatments (chemical nitrogen and potassium (NK); chemical N, P and K (NPK); and NPK plus straw (NPKS)) on the bacterial communities and P forms in sugarcane rhizosphere (RS) and bulk soils (BS) were evaluated. Compared with the NK, the NPK and NPKS treatments significantly (P<0.05) increased the yield and quality characters of sugarcane, especially under NPKS. Additionally, P fertilization significantly increased the available P (AP), soluble inorganic P (Pi) and retained Pi in both the RS and BS, but they significantly increased the Chao1 and Shannon index only in the BS; and almost all these indices were significantly higher in the RS than in the BS. The bacterial community compositions were also significantly altered by P fertilization, with major changes in the RS and minor changes in the BS. The bacterial genera that were enriched in the sugarcane rhizosphere mainly included Bradyrhizobium, Rhodanobacter, Pseudolabrys, Conexibacter, and Burkholderia-Caballeronia-Paraburkholderia, some of which potentially promote the plant growth. Compare to NK, functional groups involved in the cycling of carbon, N, and sulfur significantly increased or decreased with fertilizer P application. Moreover, the relative abundances of many bacterial species were significantly correlated with the soil P forms. In conclusion, long-term P fertilization altered bacterial structure and functions in P-deficient sugarcane soil, which could help the soil P cycling and suppling. The results provide useful information to stimulate the power of the microbes by fertilization measures to improve soil nutrients and crop production.